“Concept mapping – an innovative approach to learning” - Paul, Preetha; Easuraj, Rajarajan; Arumugam, Sasikumar; Srirangaramasamy, Jamunarani (Bangladesh Journal of Medical Science, 2021)
Background:For a medical student to blossom into a competent doctor with critical thinkingand decision-making skills, appropriate learning techniques that will enhance his learning anddevelop higher-order thinking skills are needed. Concept mapping is a learning technique thatcreates a mind map. It serves to represent information in a structured format with appropriate linkage and sequencing. Objective:This article describes a concept mapping workshop that wasorganized in our institution, our pre- and post-test results and the feedback we received. Materialsand methods:An innovative workshop on “Learning by concept mapping” was organized forfirst year MBBS students. Twelve facilitators and 150 students participated. The workshopbegan with an introductory talk on concept mapping. Then, a demonstration on how to createconcept maps was given. This was followed by a hands – on session where the students createdtheir own concept maps under the guidance of facilitators. Pre- and post-tests were administeredand feedback on the workshop was taken. Results and Discussion:Statistical analysis showedsignificant improvement betweenpre- and post-test scores. Participants appreciated the workshopand felt that concept mapping was an innovative way of learning and could help in assimilatingcomplicated subject matter. Conclusion:Concept mapping, asa learning technique, can lead toa meaningful learning experience. Such innovative approaches to learning are welcomed bystudents. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.115-121